Epidemiological, Clinical, Therapeutic, and Evolutionary Aspects of Acute Kidney Damage during Severe Malaria in Children at the Borgou Departmental Teaching Hospital (Benin) (Journal of Renal and Hepatic Disorders, 2022)
Malaria is an endemic pathology with several complications, including kidney damage. The objective of this work was to study kidney damage during severe malaria in children at the pediatrics department of the Borgou Departmental Teaching Hospital (Borgou DTH), Benin in 2021. This was a longitudinal study carried out over 4 months from June 1, 2021 to September 30, 2021 (with 1 month of recruitment from June 1 to July 1, 2021) at the pediatric department of the Borgou DTH. The study included children aged 1 month–15 years, hospitalized for Plasmodium falciparum malaria with at least one clinical manifestation of malaria severity established by the World Health Organization in 2000 and whose parents had given their informed consent. The damage was established by urinary sedimentation using urine dipstick and urinary cap and serum creatinine. Acute kidney injury (AKI) was intended and classified according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria. The dependent variable was the presence of at least one clinical, biological, and functional impairment. Follow-up was regular for up to 3 months. Lost to follow-up were excluded. Predictors of occurrence were identified. Statistical difference was considered significant at P < 0.05. Of the 164 children hospitalized for severe malaria during the study period, 72 had at least one renal impairment, with a frequency of 43.90%. The average age of the children was 44.93 months. On urine dipstick, 76.39% of the patients had hemoglobinuria and 55.56% had albuminuria. Urinary cap revealed 44% granular cylindruria and 32% crystalluria. AKI was detected in 4.54% patients. Recovery was complete in all follow-up cases. The predictors of kidney damage were coma ( P = 0.017), jaundice ( P = 0.007), thrombocytopenia ( P = 0.021), and long hospital stay ( P = 0.008). Kidney damage in severe malaria is frequent. Early diagnosis and prompt treatment are fundamentals of rapid and complete recovery of kidney functions.
Keywords: children; kidney disease; malaria; predictors; Parakou